The Effectiveness of Online Learning to Improve Knowledge About Metabolic Syndrome in Pregnancy - Sri Sulistyowati; Muhammad Adrianes Bachnas; Eric Edwin Yuliantara; Anggraini, Nutria Widya Purna; Wisnu Prabowo; Supriyadi Hari Respati; Hafi Nurinasari; Robert Ridwan; Lini Astetri; Arib Farras Wahdan; Yonathan Siswo Pratomo; Vidya Ismiaulia (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Metabolic syndrome is a persistent global health problem and a risk factor for diabetes and heart disease. A metabolic syndrome that occurs during pregnancy will pose a threat to maternal and fetal health. The incidence of metabolic syndrome during pregnancy, especially in developing countries, will become a serious public health problem in the future. This study aims to assess the effectiveness of online learning in improving the knowledge of online learning participants on metabolic syndrome cases in pregnancy. Subjects and Method: This was a cross-sectional study conducted in July through Zoom online learning on Metabolic Syndrome in Pregnancy attended by 125 participants. The dependent variable was knowledge about metabolic syndrome in pregnancy. The independent variable was online learning. The data obtained from this study were in the form of pretest and post-test scores. The data were analyzed by t-test. Results: The mean score of knowledge about metabolic syndrome in pregnancy after online learning was higher (Mean= 90.8; SD= 14.05) than before (Mean= 60.08; SD= 6.94), and this was statistically significant (p= <0.001). Conclusion: Online learning is effective to improve knowledge about metabolic syndrome in pregnancy among Indonesian Obstetrics and Gynecology Association (POGI) members and young POGI members.